Human Brain and Blood N-Glycome Profiling in Alzheimer’s Disease and Alzheimer’s Disease-Related Dementias - Yu, Lei; Huo, Zhiguang; Yang, Jingyun; Palma-Gudiel, Helena; Boyle, Patricia A.; Schneider, Julie A.; Bennett, David A.; Zhao, Jinying (Frontiers in Aging Neuroscience, 2021)
Glycosylation, the process of adding glycans (i.e., sugars) to proteins, is the most abundant post-translational modification. N-glycosylation is the most common form of glycosylation, and the N-glycan moieties play key roles in regulating protein functions and many other biological processes. Thus, identification and quantification of N-glycome (complete repertoire of all N-glycans in a sample) may provide new sources of biomarkers and shed light on health and disease. To date, little is known about the role of altered N-glycome in Alzheimer’s Disease and Alzheimer’s Disease-related Dementias (AD/ADRD). The current study included 45 older adults who had no cognitive impairment (NCI) at baseline, followed and examined annually, and underwent brain autopsy after death. During about 12-year follow-up, 15 developed mild cognitive impairment (MCI), 15 developed AD, and 15 remained NCI. Relative abundances of N-glycans in serum at 2 time points (baseline and proximate to death, ∼12.3 years apart) and postmortem brain tissue (dorsolateral prefrontal cortex) were quantified using MALDI-TOF-MS. Regression models were used to test the associations of N-glycans with AD/ADRD phenotypes. We detected 71 serum and 141 brain N-glycans, of which 46 were in common. Most serum N-glycans had mean fold changes less than one between baseline and proximate to death. The cross-tissue N-glycan correlations were weak. Baseline serum N-glycans were more strongly associated with AD/ADRD compared to change in serum N-glycans over time and brain N-glycans. The N-glycan associations were observed in both AD and non-AD neuropathologies. To our knowledge, this is the first comprehensive glycomic analysis in both blood and brain in relation to AD pathology. Our results suggest that altered N-glycans may serve as mechanistic biomarkers for early diagnosis and progression of AD/ADRD.